2015
DOI: 10.1007/s40292-015-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Platelet Reactivity and Related Clinical Implications

Abstract: Many drugs are nowadays available to inhibit platelet activation and aggregation, especially in patients with acute coronary syndromes and undergoing percutaneous coronary intervention with stent implantation. Primary targets are represented by enzymes or receptors involved in platelet activation. Genetic mutations in these targets contribute to the inter-individual variability in platelet responses therefore weakening the efficacy of antiplatelet agents. High on treatment platelet reactivity is a condition ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Nitric oxide synthase 3 plays a key role in platelets function by reducing aggregation. The polymorphisms Glu298Asp and intron4 (an allele) contribute to atherosclerosis development and risk of CAD and also influence platelet reactivity in patients with acute coronary syndromes (ACS) on DAPT (20,21). Furthermore it was recently demonstrated that the effect of Glu298Asp is offset by a loading dose of DAPT in stable CAD patients undergoing elective PCI (22).…”
Section: Platelets Receptorsmentioning
confidence: 99%
“…Nitric oxide synthase 3 plays a key role in platelets function by reducing aggregation. The polymorphisms Glu298Asp and intron4 (an allele) contribute to atherosclerosis development and risk of CAD and also influence platelet reactivity in patients with acute coronary syndromes (ACS) on DAPT (20,21). Furthermore it was recently demonstrated that the effect of Glu298Asp is offset by a loading dose of DAPT in stable CAD patients undergoing elective PCI (22).…”
Section: Platelets Receptorsmentioning
confidence: 99%
“…The results of the present study suggest that through the use of the blood tryptase concentration, together with the immunohistochemical investigation for anti-tryptase antibody staining in samples from the lung, glottis, and skin (at the site of administration of medications and contrast medium), it is possible to realize a very reliable diagnostic workflow of anaphylactic death (Figure 5). In fact, previous studies reported in the literature [61][62][63][64][65][66][67][68] have not clearly expressed how to establish a specific diagnosis of anaphylactic death. This diagnostic workflow should be used to establish an anaphylactic reaction as the cause of death with a large margin of certainty.…”
Section: Discussionmentioning
confidence: 99%
“…As a major metabolizing enzyme, CYP2C19 is involved in catalyzing the bioactivation of many commonly used drugs in humans [ 1 ]. Clopidogrel is a thienopyridine derivative that has antiplatelet effects through the inhibition of platelet adenosine receptors (e.g., P2Y12) after bioactivation by the cytochrome P450 metabolic system [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%